EXPLORING LANGUAGE USED OF ENCOURAGEMENT IN THE MENTAL HEALTH CAMPAIGN ON INSTAGRAM: MODALITY MEANINGS - Yusmaniar Nur Aviva; Widyastuti (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2022)
Mental health campaigns aim to educate sufferers about the importance of mental health and how to manage it. This study investigated how the functions of language and the meaning of modality were employed in @myselflovesupply's mental health campaign posts. In this study, the descriptive qualitative approach was used to evaluate the data. The data were gathered from the words written in the Instagram posts. According to the findings, the language functions discovered in the mental health campaign consist of conative, emotive, and referential, in accordance with Jakobson's theory. In addition, the use of modality in the mental health campaign by @myselflovesupply is extensive. Examined based on Halliday and Matthiessen's theory, the study found all the data used modality; modalization and modulation obtained the same amount of data, which includes obligation, possibility, usuality, and inclination. Encouragement language in mental health campaigns can motivate and encourage sufferers to find motivation, inspiration, comfort, and aspiration, which are crucial for their mental health. The researchers suggest that exploring multiple mental health campaigns to uncover more complex results beyond what was discovered in this current study would be beneficial in future studies. This would provide additional insights and broaden existing knowledge on this topic.